Market and Stakeholders Analyses on Ecotourism in Subak Sembung, Peguyangan Village, Denpasar City - Sarjana, I Made (E-Journal of Tourism, 2016)
By developing new tourism destination, governments and people Bali want to realize sustainability tourism reached higher quality of life. Ecotourism is a part of alternative tourism which is implementing sustainable tourism ideology. Used multifunction term on optimizing rice field areas, Subak Sembung, Peguyangan Village, Denpasar City established ecotourism destination in 2015. They provide agriculture products and services to tourism who want refresh, relax, or learn farming activities in Subak Sembung’s Rice field areas by creating jogging track, pasar carik (market in rice field areas) etc. Subak sembung plants some excellent commoditie that they can grow up properly in lower areas of Bali like flower, nuts, sweet potatoes, ginger etc.
Keywords: protected, rice field, culture, ecotourism, stakeholders and marketing